Updates on the treatment of gout, including a review of updated treatment guidelines and use of small molecule therapies for difficult-to-treat gout and gout flares. (24th July 2017) - Soskind, Rose; Abazia, Daniel T.; Bridgeman, Mary Barna
ABSTRACT: Introduction : Gout is a rheumatologic condition associated with elevated serum uric acid levels and deposition of monosodium urate crystals in joints and soft tissues. Areas covered : In this article, we describe the role of currently available drug therapies for managing acute gout flares and used in reducing serum urate levels. Further, we explore the role of novel small molecular therapies and biologic agents in the treatment of refractory or severe gout symptoms. A literature search of MEDLINE and MEDLINE In-Process & Other Non-Indexed Citations Databases (1996-June 2017) was conducted utilizing the key words 'gout', 'interleukin-1 inhibitors', 'acute gout', 'gout treatment', 'urate lowering therapies', 'hyperuricemia', 'colchicine', 'pegloticase', 'lesinurad', 'xanthine oxidase', 'xanthine oxidase inhibitors', 'allopurinol', 'febuxostat', 'uricosurics', 'probenecid', and 'benzbromarone'. All published articles regarding therapeutic management of gout and hyperuricemia were evaluated. References of selected articles, data from poster presentations, and abstract publications were additionally reviewed. Expert opinion : Numerous therapies are currently available to managing acute gout flares and for lowering serum urate levels; advances in the understanding of the pathophysiology of this disorder has led to the emergence of targeted therapies and novel biologic preparations currently in development which may improve the clinical management of severe or refractory cases of disease that fail to respond to traditional therapies.